DAMPAK KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP PERILAKU KEWARGANEGARAAN ORANISASI PADA PANTAI WISATA LON MALANG - Sherly Yulianti; Samsuki Samsuki (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the impact of transformational leadership and organizational culture on organizational citizenship behavior (OCB) at Lon Malang Tourism Beach in Sampang Regency, Madura Island. In the competitive tourism industry, OCB is important to improve service quality and visitor experience. The method used is a quantitative method with primary data collection from 38 employees through questionnaires. The results of the analysis show that effective transformational leadership can motivate employees to go beyond their formal duties, while a positive organizational culture produces a work atmosphere that supports active engagement. These findings emphasize the need to develop management strategies that focus on improving leadership and organizational culture to encourage OCB, so as to improve employee performance and visitor satisfaction in the tourism sector